Analisis Umur Pemakaian Transformator Distribusi 20 kV di PT Krakatau Tirta Industri - Agung Rizky Jamas; Desmira Desmira (Jurnal Rekayasa Proses dan Industri Terapan, 2025)
Power station generates electricity that must be distributed through the electrical distribution system, the condition of existing and adequate electrical power equipment should be the reliability and stability of the system is guaranteed to provide comfort in service to consumers. One of the most powerful sources of electrical power that has been used is the power distribution system commonly referred to as a transformer. This research uses a survey research design that ignores or does not change/modify any variables. The form of facts in the form of data needed to be able to identify a calculation includes the fact of a distribution transformer data and facts in the form of peak loading data (every 4 hours). Based on statistics, there are a total of 4 transformers consisting of three-phase transformers with a capacity (rating) of 20kVA. All transformer units operate at loads greater than 80%. from the analysis of the data presented 1. Predicted remaining life of distribution transformers that are loaded above 80% of the transformer capacity in Substations II and IV of Cilegon city, is 39.12 years. 2. From the calculation results, it is predicted that the service life of distribution transformers that are loaded above 80% of the transformer capacity at Krenceng Substations II and IV of CIlegon city is 39.12 or 20 years.